1972
DOI: 10.1172/jci106947
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous study of the metabolic turnover and renal excretion of salivary amylase-125I and pancreatic amylase-131I in the baboon

Abstract: A B S T R A C T The metabolic turnover of salivary and pancreatic amylase was studied in the baboon, an animal with a serum amylase level and renal clearance of amylase similar to man. Purified amylase was electrolytically iodinated. Although iodinated and uniodinated amylase had similar gel filtration, electrophoretic, enzymatic, glycogen precipitation characteristics, the labeled enzyme was cleared less rapidly by the kidney than was the unlabeled material. However, urinary iodinated amylase which had been b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
3

Year Published

1977
1977
1993
1993

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(11 citation statements)
references
References 13 publications
1
7
0
3
Order By: Relevance
“…These findings are in agreement with former observations on amylase excretion in the baboon [3], but not with those in humans [6,7], They fit the theory of protein excretion, according to which size and charge are impor tant determinants of glomerular filtration of proteins [15,16]. The difference in the reab sorption rate, however, is unlikely to be caused solely by differences in molecular charge [17][18][19], Thus, Wetzels et al [7] re ported on a higher renal clearance of P-(pi 7.0) than of S-amylase (pi 5.9-6.4) in hu mans.…”
Section: Resultssupporting
confidence: 94%
“…These findings are in agreement with former observations on amylase excretion in the baboon [3], but not with those in humans [6,7], They fit the theory of protein excretion, according to which size and charge are impor tant determinants of glomerular filtration of proteins [15,16]. The difference in the reab sorption rate, however, is unlikely to be caused solely by differences in molecular charge [17][18][19], Thus, Wetzels et al [7] re ported on a higher renal clearance of P-(pi 7.0) than of S-amylase (pi 5.9-6.4) in hu mans.…”
Section: Resultssupporting
confidence: 94%
“…Deficiency of the essential amino acid tryptophan, diminished amylase production, and administration of puromycin, a specific inhibitor of protein synthesis, caused a cessation of amylase production by the liver. In the dog, the liver appears to produce amylase (Nothman and Callow, 1971), and, in the baboon, Duane et al (1972) showed that the liver was a major site of amylase destruction.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for the delayed return of elastase 1 to its normal level in comparison with amylase remains unclear. The half-life of amylase has been reported to be 1-4 h in experimental studies [13][14][15][16], Elas tase 1 exists in the blood in a complex form either with ai-antitrypsin or with cti-macroglobulin [17]. The ai-Antitrypsin-bound form of elastase 1 was measured with the radioimmunoassay technique used in the present study [ 18].…”
Section: Discussionmentioning
confidence: 99%